Sleepless city - Coleman, Reed Farrel, 1956- (Coleman, Reed Farrel, 1956- Nick Ryan series., 2022)
"Every cop in the city knows his name, but no one says it out loud. In fact, they don't talk about him at all. He doesn't wear a uniform, but he is the most powerful cop in New York. Nick Ryan can find a criminal who's vanished. Or he can make a key witness disappear. He has cars, safe houses, money, and weapons hidden all over the city. He's the mayor's private cop, the fixer, the first call when the men and women who protect and serve are in trouble and need protection themselves. With conflicted loyalties and a divided soul, he's a veteran cop still fighting his own private war. He's a soldier of the streets with his own personal code. But what happens when the man who knows all the city's secrets becomes a threat to both sides of the law?"--